Effects of vector leptoquarks on decay. (January 2021) - Azizi, K.; Olgun, A. T.; Tavukoğlu, Z.
Abstract: Experimental data on, , and, provided by different collaborations, show sizable deviations from the standard model predictions. To describe these anomalies, many new physics scenarios have been proposed. One of them is the leptoquark model, which introduces the simultaneous coupling of vector and scalar leptoquarks to quarks and leptons. To look for similar possible anomalies in the baryonic sector, we investigate the effects of a vector leptoquark on various physical quantities related to the tree-level decays ( ), which proceed via transitions at the quark level. We calculate the differential branching ratio, forward-backward asymmetry, and longitudinal polarizations of leptons and baryons at the and lepton channels in the leptoquark model and compare their behavior to the predictions of the SM in terms of . In the calculations, we use the form factors calculated in full QCD as the main input and account for all errors coming from the form factors and model parameters. We observe that at the channel, the fit solution to data related to the leptoquark model sweeps some regions out of the SM band; nevertheless, the fit has a considerable intersection with the SM predictions. The type solution gives roughly the same results as the SM on . At the channel, the leptoquark model gives results that are consistent with the SM predictions and existing experimental data on the behavior of with respect to . Concerning the behavior of the, the two types of fits for and the predictions at the channel in the leptoquark model give exactly the same results as the SM. We also investigate the behavior of the parameter with respect to and the value of in both the vector leptoquark and SM models. Both fit solutions lead to results that deviate considerably from the SM predictions for and . Future experimental data on and, made available by measurements of the channel, will be particularly helpful. Any experimental deviations from the SM predictions in this channel would emphasize the importance of tree-level hadronic weak transitions as good probes of new physics effects beyond the SM.